State and market integration in China: A spatial econometrics approach to 'local protectionism' - Carsten Herrmann-Pillath; Alexander Libman; Yu Xiaofan (Frankfurt School of Finance & Management, 2010)
In the past two decades, controversial evidence has been produced supporting the case for local protectionism in China. This paper overviews the most important contributions and presents a new approach which applies spatial econometrics on prefectural-level data. The main advantage of this method is to rely on a theoretically less biased and internal benchmark for assessing the impact of provincial borders on spatial interdependences, as we compare within province and across province growth spillovers for neighbouring prefectures. We show that provincial borders exert a strong impact on spillovers. Further, we also analyze spillovers of local public expenditures, which could be interpreted as proxies for government interventions. Again, provincial borders matter. Yet, we are cautious in interpreting this as evidence for local protectionism, and propose the notion of 'cellularity' as an alternative explanation. Cellularity results from a confluence of different factors, such as administrative structure, institutional changes and regional culture.
Keywords: H7; O18; P23; P26; R11; 330; Domestic market integration in China: local protectionism; spatial econometrics; growth spillovers; expenditure spillovers; cellularity